2020
DOI: 10.1002/lary.28543
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cisplatin‐related and Age‐related Hearing Loss During an Extended Follow‐up

Abstract: ObjectivesCisplatin‐related hearing loss (HL) is claimed to progress after treatment. This controlled longitudinal study with extended follow‐up investigates HL in testicular cancer survivors (TCSs) after cisplatin‐based chemotherapy (CBCT).Study DesignControlled longitudinal study.MethodsEighty‐two TCSs treated with CBCT between 1980 and 1994 in Norway participated in two surveys (S1/S3), including pure‐tone audiograms (0.125–8 kHz) and self‐reported HL, 12 and 31 years after treatment, respectively. Hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Some cancers, such as testicular cancer (TC), are identi ed in young adulthood, thus the retention of cisplatin in the cochlea is especially troubling as these patients have upwards of 50 years of lifespan ahead of them. A 2018 study (Haugnes et al, 2018) found a signi cant effect of cisplatin-related hearing loss that exacerbated age-related hearing loss in TC survivors; however, in a con icting later study from this group (Skalleberg et al, 2020), age-related hearing loss appeared similar to cisplatin-related hearing loss, supporting the theory that cisplatin may not exacerbate age-related hearing loss. Regardless of the mechanism(s) of action of cisplatin-related hearing loss, there is increased concern for the potential longterm consequences of hearing loss that have been reported in the general population, including clinicallyrelevant decreases in communication and health-related quality of life (Carabellese et al, 1993;Chia et al, 2007;Dalton et al, 2003;Mulrow et al, 1990) Thus, hearing loss and tinnitus related to cisplatin-based chemotherapy are important to understand in cancer survivorship.…”
Section: Introductionmentioning
confidence: 95%
“…Some cancers, such as testicular cancer (TC), are identi ed in young adulthood, thus the retention of cisplatin in the cochlea is especially troubling as these patients have upwards of 50 years of lifespan ahead of them. A 2018 study (Haugnes et al, 2018) found a signi cant effect of cisplatin-related hearing loss that exacerbated age-related hearing loss in TC survivors; however, in a con icting later study from this group (Skalleberg et al, 2020), age-related hearing loss appeared similar to cisplatin-related hearing loss, supporting the theory that cisplatin may not exacerbate age-related hearing loss. Regardless of the mechanism(s) of action of cisplatin-related hearing loss, there is increased concern for the potential longterm consequences of hearing loss that have been reported in the general population, including clinicallyrelevant decreases in communication and health-related quality of life (Carabellese et al, 1993;Chia et al, 2007;Dalton et al, 2003;Mulrow et al, 1990) Thus, hearing loss and tinnitus related to cisplatin-based chemotherapy are important to understand in cancer survivorship.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, monitoring of cochleotoxic effects of cisplatin is advised and implemented in clinical practice ( Brooks and Knight, 2017 ; Clemens et al, 2019 ; Sprouse and Gozdecki, 2019 ). Age- and sex-adjusted audiometry is also suggested in long-term follow-up of adult cancer survivors to minimize the effects of age-related hearing loss ( Skalleberg et al, 2020 ).…”
Section: Clinical Data Of Cisplatin Ototoxicitymentioning
confidence: 99%
“…Our findings show that for patients with self-reported HL after CBCT but normal audiometric findings (0.25 to 8 kHz), referral to an audiologist for additional testing and inclusion of EHFs should be encouraged. This is especially important in relatively young TCS, since they are less likely to experience the deficits in EHFs that accompany aging (Skalleberg et al 2020). To our knowledge, there are no follow-up guidelines for audiometric assessments in CBCT-treated adult-onset cancer survivors.…”
Section: Discussionmentioning
confidence: 99%